Effect of ion implantation on the physical and mechanical properties of Ti-Si-N multifunctional coatings for biomedical applications. (15th November 2016) - Shypylenko, A.; Pshyk, A.V.; Grześkowiak, B.; Medjanik, K.; Peplinska, B.; Oyoshi, K.; Pogrebnjak, A.; Jurga, S.; Coy, E.
Abstract: In the present work, multifunctional Ti-Si-N coatings have been deposited using CAVD method with the aim of studying their chemical, physical, structural and mechanical properties. Coatings of Ti-Si-N were modified by high-intensity ion implantation using copper ions with dose D = 2 × 10 17  ions/cm 2 and energy E = 60 keV. The results demonstrated that ion implantation has an effect on the grain size, hardness, and Young modulus of the Ti-Si-N coating. Additionally, the effect of Cu implantation on the bioactive properties of coatings was investigated by contact antimicrobial essay. The results show a high release of Cu ions in the cultivation liquid and the low efficiency of the < 20% Cu doping towards E. coli bacteria. Our results bring understanding to the low dosage ion implantation of multifunctional surfaces towards applications and general drawbacks of ion implantation as bioactive tailoring method. Graphical abstract: Highlights: Ternary coatings of the Ti-Si-N system were deposited by CAVD method. Cu ions with energy of 60 keV and dosage of D = 2 × 10 17  ions/cm 2 were implanted. A Cu concentration of up to 25% at a depth of 25 nm (maximum implantation depth of 60 nm) was achieved. Mechanical properties of the coating have been negatively affected by ion implantation. The low dosage of Cu ions did not show any antibacterial activity on the samples, while a rapid release of Cu was observed.